Phytotoxicity of organic extracts of five medicinal plants of the Neotropical savanna - Pinto, G. F.S. [UNESP]; Roma, L. P.; Kolb, R. M. [UNESP] (FapUNIFESP (SciELO), 2023)
Medicinal plants produce a high diversity of secondary metabolites with different biological activities, which are commonly evaluated when prospecting for bioherbicides. We analyzed the phytotoxic activity of organic extracts from the leaves of five medicinal species, Byrsonima intermedia, Moquiniastrum polymorphum, Luehea candicans, Miconia chamissois, and Qualea cordata. Phytotoxicity was evaluated on the initial growth of cucumber seedlings through tests with different concentrations of hexane, ethyl acetate, and methanol extracts. The results showed that all organic extracts and all concentrations affected cucumber development, with methanol extracts generally showing the greatest negative effect on the initial growth of the target species. The only exception was for M. chamissois extracts, in which the hexane extract had the greatest phytotoxicity. Furthermore, the organic extracts were subjected to preliminary phytochemical analysis, revealing the widespread presence of alkaloids along with other chemical classes. All the study species are thus potential candidates for use as natural herbicides.
Fitotoxicidade de extratos orgânicos de cinco plantas medicinais do Cerrado
Keywords: Cerrado; cucumber initial growth; leaf extract; phytochemical screening